The new legal realism. edited by Elizabeth Mertz, Stewart Macaulay, Thomas W. Mitchell. - Macaulay, Stewart, 1931-; Mertz, Elizabeth; Mitchell, Thomas W. (Cambridge University Press, 2016)
This is the first of two volumes announcing the emergence of the new legal realism as a field of study. At a time when the legal academy is turning to social science for new approaches, these volumes chart a new course for interdisciplinary research by synthesizing law on the ground, empirical research, and theory. Volume 1 lays the groundwork for this novel and comprehensive approach with an innovative mix of theoretical, historical, pedagogical, and empirical perspectives. Their empirical work covers such wide-ranging topics as the financial crisis, intellectual property battles, the legal disenfranchisement of African-American landowners, and gender and racial prejudice on law school faculties. The methodological blueprint offered here will be essential for anyone interested in the future of law-and-society.